Determining the lines of system maturity, system readiness and capability readiness in the system development lifecycle - Tetlay, Abideen; John, Philip (Published and used by CSER 2009 with permission, 2009)
Many systems suffer from major problems with implementation, integration, performance and other lifecycle problems and unexpected and unacceptable behaviour often arises when they are introduced into the real world, yet the systems were believed to be “ready” for use. Often, certain aspects about the real world context are not always appreciated until surprise problems arise when the system is introduced and used. This could be thought of as a failure in “systems understanding”. We are not good enough at understanding system implementation and integration issues (in their widest sense) and the associated Risk issues in assessing a System‟s Maturity and Readiness within a development programme and overall lifecycle. This challenge is increasing interest and emphasis on System Maturity assessments and in the use of System Readiness Levels and on achieving the overall Capability of a system in its intended operational environment. In this paper, we investigate the issues by addressing the following key questions: Why are “Maturity” and “Readiness” important in Systems Engineering (SE)? Is there a sufficiently clear distinction between „System Maturity‟ (SM) and „System Readiness‟ (SR)? What do we mean by SM and SR? How is the term „Capability‟ currently being used in SE? Why do we need to assess the Capability of the system? What do we mean by „Capability Readiness‟ (CR)? We define SM, SR and CR and map these to the System Development and overall Lifecycle and then provide recommendations for further research.
Keywords: System Maturity; System Readiness; Capability Readiness; System Development Lifecycle